Strategies and foundations for scientific discovery in longitudinal studies of bipolar disorder. (18th March 2022) - McInnis, Melvin G.; Andreassen, Ole A.; Andreazza, Ana C.; Alon, Uri; Berk, Michael; Brister, Teri; Burdick, Katherine E.; Cui, Donghong; Frye, Mark; Leboyer, Marion; Mitchell, Philip B.; Merikangas, Kathleen; et al.
Abstract: Bipolar disorder (BD) is a complex and dynamic condition with a typical onset in late adolescence or early adulthood followed by an episodic course with intervening periods of subthreshold symptoms or euthymia. It is complicated by the accumulation of comorbid medical and psychiatric disorders. The etiology of BD remains unknown and no reliable biological markers have yet been identified. This is likely due to lack of comprehensive ontological framework and, most importantly, the fact that most studies have been based on small nonrepresentative clinical samples with cross‐sectional designs. We propose to establish large, global longitudinal cohorts of BD studied consistently in a multidimensional and multidisciplinary manner to determine etiology and help improve treatment. Herein we propose collection of a broad range of data that reflect the heterogenic phenotypic manifestations of BD that include dimensional and categorical measures of mood, neurocognitive, personality, behavior, sleep and circadian, life‐story, and outcomes domains. In combination with genetic and biological information such an approach promotes the integrating and harmonizing of data within and across current ontology systems while supporting a paradigm shift that will facilitate discovery and become the basis for novel hypotheses.